Peer Holm Jorgensen’s work, The Missing History: Based on the True Story of Dewa Soeradjana - I Ketut Ardhana (International Journal of Interreligious and Intercultural Studies, 2021)
This article was originally a paper when the author was asked to discuss Peer Holm Jorgensen’s work, The Missing History: Based on the True Story of Dewa Soeradjana, which was organized by the Bali Study Center-Udayana University in collaboration with Bentara Budaya. The title given by the author in connection with the discussion of the contents of the book is assesing the Witness of a Person in History Before the Events of September 30, 1965. It should be noted that until now, the development of Indonesian historiography is still far from the expectation of writing a complete and comprehensive history. This is because in addition to the limited historical sources available relating to the periods made in the writing of Indonesian history itself, such as between the classical historical period, modern history and contemporary history which entered into the realm of cultural studies as the post-modern era. The existence of gaps between these periods, especially in the post-revolutionary period, seems to be caused by the spirit of the times that developed after the end of the New Order era, where there was a demand for a forward total history writing. This means that there is now a demand for an open history writing, without any cover-up, so that Indonesian society in general and historians (professional historians), history enthusiasts, amateur historians, and students will be able to fully understand the history of their nation. The hope that this demand will get a chance, now that the New Order regime which ruled for more than 32 years in a centralized and authoritarian manner has ended. The hopes include the need to represent studies related to the demands of the reform era which want transparency, accountability, openness and provide defense to minority groups, and marginalized people as a result of policies that benefit the majority group. This condition gave the majority group an opportunity to legitimize its power, various strategies are carried out so that it was hoped that it would not provide opportunities for political groups or opponents to defend themselves.